Pediatric Care in São Tomé and Príncipe: A Different Reality: Cuidados Pediátricos em São Tomé e Príncipe: Uma Realidade Diferente - Medeiros, Inês de; Carvalho, Fábia (Gazeta Médica, 2017)
Pediatric care in developing countries takes on a different and more conscious reality when sensed in the first person. Living and feeling the daily difficulties in São Tomé and Príncipe is having a greater awareness of real challenges and needs of the country. The difficulties felt and the lack of medical resources contributed to a more genuine practice of medicine and to the return to pure clinical semiology; a remarkable and challenging experience in pediatric clinical practice.